Pengembangan Ekonomi Kreatif Dalam Bank Sampah Syariah (BSS) Pesisir Untuk Mewujudkan Masyarakat Madani THE DEVELOPMENT OF CREATIVE ECONOMY IN THE ISLAMIC WASTE BANK TO REALIZE CIVIL SOCIETY - Iklimah, Iklimah; khatijah, Siti (Universitas Trunojoyo Madura, 2017)
The creative economy is synonymous with the idea and management of waste banks in it must be accompanied by various ideas or ideas of progress so that later they will not lose in the arena of global competition. That, will be an alternative to minimize waste scattered along Branta village, especially on the lips of the Branta Coast and will in fact realize the Madani community so that later halal life styles will still exist in the Madurese community in general and the Branta community in particular.The formulation of the problem in accordance with the context is how is the creative economic development system of the coastal Sharia Bank and what is the concept of managing the sharia coastal bank in Branta Class III to adopt the Madani community? Therefore the goal can easily be known to find a good and suitable system in developing the creative economy in the form of coastal waste banks and to know what concepts and how to manage pesisr waste banks which will eventually facilitate the realization of civil society.The research method we used in this study is a qualitative descriptive methodology in which the data sources we obtain are primary data through observation, interviews and documentation from Branta residents and Branta coastal officers are also equipped with secondary data from various websites, journals, books, articles etc.The results of this research are that the development of creative economy in Islamic sharia banks will not run smoothly if there is a lack of role of the three figures, besides that the products from the Islamic waste bank offered are quite varied.